NEW PRODUCT DEMAND FORECASTING AND INVENTORY MODEL TOWARDS EYEWEAR CLEANSER PRODUCT: A CASE STUDY OF NASHO COMPANY - Salsabilla
Nanotechnology in optical business is showing the occasion based on the compound annual growth rate for 8.3% from 2016 – 2021. Besides, the glasses as the optical device has an opportunity to increase based on the report that Indonesian has 2-3 glasses. Then, the increasing of glasses needs in line with the increasing of myopia suffer up to 50% in the world population. Nasho Company is inspired to make self-cleaning product utilize nanotechnology based on the problem that exists from the glasses user, such as dirty lenses and dewy lenses. The Company desired to expand the market by entering the product into the glasses shop. The Company already found the occasion by the owner of the glasses shop interest to sell Nasho product into the shop. Nevertheless, the productivity and efficiency of production in this company are low due to unplanned production as well as order the material just when demand come. Moreover, Nasho, as a new product, would deal with the dynamic of demand, product lifecycle, as well as another variant from competitors. Production planning and inventory model is required for solving this problem. New product forecasting is required to decrease the new product risk as well as the plan based. Analogy Forecasting is purposed to analyze the historical data trend and define the sales pattern of the new product by merging judgmental and statistical processes to represent the new product forecasting from the past product. As a result, this method would define similar demand forecasting for a new product. This research using 6-step Structured Analogy Forecasting by Gilliland & Guseman. For optimizing the inventory level, this research uses safety stock for against the variation of demand during the order interval and lead time with targeted service level. Then, the inventory model used is Fixed Interval Ordering, which defines the number of materials stocking with a time that set up. As a result of Structured Analogy forecasting; in judgmental process, the benchmark product is Expo lenses cleaner using the judgmental process with thematic analysis meanwhile for statistical process, Single Exponential Smoothing with ?= 1,92215 is applied with MAPE 6,42%, MAD= 59,68, and MSD= 5362,4, as well as demand in next year, would be 10631 bottles of lenses cleaner liquid. By 95% service level which means there 5% approximation of material stock out, safety stock for each material are; 2 l of Ethanol, 1 l of Polydimethylsiloxane, 0,1 l of Isopropyl, 116 unit of bottle, 2 boxes of wiper, 29 A3+ sheets of Box, 4 A3+ sheets of the sticker, and 7 sheets of 1 m HVS of Instruction Paper. As the result of Fixed Order Interval, the Company would order; 14 l of Ethanol, 2,5 l Polydimethylsiloxane, 2 l of Isopropyl, 870 unit of the bottle, 13 boxes of wiper, 207 A3+ sheets of Box, 25 A3+ sheets of the sticker, and 47 sheets of 1 m HVS of Instruction Paper in every 14 working days. As the implication of forecasting results and inventory model, the Company is able to improve production productivity and efficiency as well as set the target due to market expansion. It would assist each division in Nasho Company to construct its plan due to market expansion. Thus, this market expansion would be more efficient.